Novel Copper(I) Clusters with 2‐(Diphenylphosphanyl)anilide Ligands. Synthesis and Crystal Structures of [Cu6X2(NHR)4] (X = Cl, Br, I; R = C6H4‐2‐PPh2). Issue 2 (5th December 2016) - Liebing, Phil; Freudenberg, Jan; Heiser, Christian; Merzweiler, Kurt
Abstract : Treatment of copper(I) halides Cu X ( X = Cl, Br, I) with lithium 2‐(diphenylphosphanyl)anilide [Li(HL)] in THF led to the formation of hexanuclear copper(I) complexes [Cu6 X 2 (HL)4 ] [ X = Cl (1 ), Br (2 ), I (3 )]. In compounds1 –3, the copper atoms are in a distorted octahedral arrangement and the amide ligands adopt a μ3 ‐κP, κ 2 N bridging mode. Additionally there are two μ2 ‐bridging halide ligands. Each of the [Cu6 X 2 (HL)4 ] clusters comprises two copper atoms, which are surrounded by two amide nitrogen atoms in an almost linear coordination [Cu–N: 186.2(3)–188.0(3) pm] and four copper atoms, which are connected to an amide N atom, a P atom, and a halogen atom in a distorted trigonal planar fashion [Cu–N: 199.6(3)–202.3(3) pm)]. Abstract :